Cockfosters - Simpson, Helen 1957- (Jonathan Cape, 2015)
Cockfosters is a funny, frank and forceful story collection dealing with ageing, ambition and the patterns of repetition and renewal found in long friendships and marriages. It opens irresistible new windows onto the world from Arizona to Dubai and from Moscow to Berlin. Turning both a panoramic and a zoom lens on the way we live now, these stories range through hitch-hiking in Bohemian forest-land to cresting the waves of the Aegean to the mending of hearts and the recovery of lost property at the end of the Piccadilly Line. Helen Simpson writes with great warmth, wit and candour about the complexities of modern life, and this new collection shows why she is hailed as one of the best short story writers at work in the world today
Keywords: Friendship -- Fiction; Married people -- Fiction; Conduct of life -- Fiction; Fiktionale Darstellung